The Use of Fanpage Counseling through Information Service Model at Junior High School - Agung Kuriawan; Epin Candra Buana (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Information technology has become an integral part of various sectors of life, including education. In particular, it has influenced the delivery of guidance and counseling services, enabling new models of communication and interaction between counselors and students. Objective: This study aimed to determine the model of information services and examine its influence through the use of Fanpage Counseling on Facebook at SMP Negeri 1 Gurah. Method: This research employed a quantitative approach with a correlational method. The study was conducted in 2022 at SMP Negeri 1 Gurah, involving a sample of 18 students. Result: The findings revealed that the use of a Facebook Fanpage had a significant influence on the delivery of guidance and counseling information services at SMP Negeri 1 Gurah. Conclusion: The study concluded that the use of Facebook Fanpage by students facilitates the delivery of school counseling information and positively influences student engagement with the service. Contribution: This research contributes new insights and practical knowledge regarding the implementation of information service models through social media, particularly Fanpage Counseling, in school settings.